MR imaging of rectus femoris origin injuries - Ouellette, Hugue; Thomas, Bijoy J.; Nelson, Erik; Torriani, Martin (Skeletal radiology, 2006)
To describe the MR imaging findings of acute and chronic rectus femoris origin (RFO) injuries. A retrospective review of pelvic and hip MR imaging procedures was performed over a 4-year period for detection of cases with injuries to the RFO. Subjects were classified as having either acute or chronic symptoms. MR imaging studies, radiographs, CT scans, radiology reports, medical records, and operative notes were reviewed. Imaging analysis was directed to assess injuries affecting the direct and indirect heads of the RFO. Concurrent osseous, cartilaginous and musculotendinous injuries were tabulated. The incidence of RFO injuries on MR imaging was 0.5% (17/3160). With the exception of one case of anterior inferior iliac spine apophysis avulsion and partial tear of the direct head of RFO, all subjects had indirect head of RFO injuries (acute injury 8/9, chronic injury 8/8). Partial tear of the direct head of RFO was less frequently seen (acute injury 3/9, chronic injury 2/8). Partial tears of the conjoint tendon were least frequent (acute 1/9, chronic 2/8). No full-thickness tears of the RFO were noted. Associated labral tears were seen in only one case, with no other concomitant abnormality of the articular cartilage or surrounding soft tissues. All RFO injuries were treated non-operatively. Injuries of the RFO are uncommon on MR examinations of pelvis/hips and may occur in a sequence progressing from indirect head injury to involvement of direct head and conjoint tendon in more severe cases.